Pengaruh Kepuasan Kerja Dan Kompensasi Terhadap Stres Kerja Karyawan Pt. Sari’ - Winniecia Winniecia; Syawaluddin Syawaluddin; Thomas Sumarsan Goh (Economics and Digital Business Review, 2023)
PT. Sari is a restaurant that has a distinctive interior design, which is a combination of blue and red colors with wood elements in the furniture found in almost all of their outlets. The workload that employees receive while working in the company makes employees feel pressured because it is based on the experience possessed by employees. Compensation given by the company to its employees is still considered standard and some are still almost equivalent to the UMK currently in effect in the city of Medan, making employees feel that the compensation they currently receive is not appropriate. Employees complained about the lack of satisfaction they had while working in the company because uncomfortable working conditions caused some employees to be lazy to complete their work. The research population that will be used in the study are: all 364 employees of the company. Based on calculations using the Slovin formula, it can be seen that the number of samples obtained was 78 samples where the tolerance level used 10% due to time and energy limitations from the researchers so that the researchers reduced the number of samples from a tolerance level of 5% to 10%. Simultaneously there is a significant influence between the variables of job satisfaction and compensation on the work stress of employees of PT. Sari. While partially found the variable job satisfaction has a significant effect on the work stress of employees of PT. Sari. Partially it was found that the compensation variable had a significant effect on the work stress of PT. Sari. The results of this study indicate that the compensation variable has more influence than job satisfaction on the work stress of PT. Sari.